Uncovering Maqoshid Sharia: Safeguarding Ethics in Islamic Economics - Kaira, Lamin; Mohammed, Gehad; Arum, Nurlita; Hardina, Lulu; Nur Rahman, Arif; Danang Saputra, Aditya (Inovasi Analisis Data, 2024)
This study investigates the relationship between maqoshid sharia and economic practices in Indonesia, aiming to provide insights into how Islamic principles can contribute to sustainable and inclusive economic development. Utilizing a qualitative research methodology grounded in post-positivism, the study examines 89 publications from 2019 to 2023, employing descriptive statistics and an inductive approach to ensure nuanced interpretations. The research highlights the role of maqoshid sharia in adapting Islamic law to contemporary social dynamics, promoting human welfare, and guiding sharia application in economic practices. It categorizes maqoshid sharia into Dharuriyat (necessities), Hajiyat (needs), and Tahsiniyat (enhancements), emphasizing their importance in achieving socio-economic justice. Key contributions in the field include studies on corporate social responsibility, Islamic banking performance, and the foundations of Islamic finance. A bibliometric analysis with VOSViewer maps the development of maqoshid sharia research, identifying major clusters and collaboration patterns among authors. Overall, this study underscores the critical role of maqoshid sharia in shaping ethical economic practices in Indonesia, offering a comprehensive understanding of the interplay between religion, ethics, and economics in a multicultural context, with significant implications for public policy and economic strategies.